Uji Aktivitas Antibakteri Ekstrak Etanol Daun Rambutan (Nephelium lappaceum L) Pada Pertumbuhan Bakteri Staphylococcus aureus dan Escherichia coli - Nina Irmayanti Harahap (Jurnal Penelitian Farmasi & Herbal, 2022)
The purpose of this study was to determine that the ethanolic extract of rambutan leaves (Nephelium lappaceum L) has antibacterial activity against Staphylococcus aureus and Escherichia coli bacteria. As an antibacterial comparator used Amoxicillin. Each leaf of sample was extracted with maceration methode using 70% of ethanol solvent. Where it 2 to 3 days with several stirring times then it filtered, then the filtrate result was thickened with vacuum rotary evaporator. The antibacterial activity test used the paper disc diffusion method and was observed based on the diameter of the inhibition zone or the clear zone formed around the paper discs and slots which used with three times treatments. Result test of antibacterial activity of rambutan leaf ethanol extract (Nephelium lappaceum L) with these method showed that the extract actively inhibited the growth of Staphylococcus aureus bacteria with Minimum Inhibitory Concentration (MIC)3.125% with a 7.96 mm, but not showed for the growth of Escherichia coli bacteria.